PENGARUH NEGOSIASI DEBT CONTRACTS, POLITICAL COST, FIXED ASSET INTENSITY, DAN MARKET TO BOOK RATIO TERHADAP PERUSAHAAN MELAKUKAN REVALUASI ASET TETAP (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2014) - Latifa, Cut Annisa; Haridhi, Musfiari (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
The purpose of this research is to determine the influence of debt contracts, political cost,, fixed asset intensity and market to book ratio to revaluation of fixed asset in manufacture companies listed in Indonesia Stock Exchange (BEI) during 2010 until 2014.The method used in this research is purposive sampling method. The sample of this research is manufacture companies listed in Indonesia Stock Exchange during 2010 until 2014, there are 86 manufacture companies observations fulfilling the sample criteria. The analysis method used in the research is logistic regression analysis.The result of this research shows that (1) debt contracts has negatively effect on fixed asset revaluation (2) political cost has no significant effect on fixed asset revaluation (3) fixed asset intensity has positively effect on fixed asset revaluation (4) market to book ratio has positively effect on fixed asset revaluation.Keywords fixed asset revaluation, debt contracts, political cost, fixed asset intensity and market to book ratio